Prevalence and associated factors of depression among adolescent boys and girls in Bangladesh: Findings from a nationwide survey - Mridha, Malay Kanti; Hossain, Md Mokbul; Khan, Md Showkat Ali; Hanif, Abu Abdullah Mohammad; Hasan, Mehedi; Mitra, Dipak; Hossaine, Moyazzam; Ullah, Mohammad Aman; Sarker, Samir Kanti; Rahman, S M Mustafizur; Bulbul, Md M Islam; Shamim, Abu Ahmed (BMJ Journals, 2022)
This article was published in BMJ Open by BMJ Journals [© Author(s) (or their employer(s)) 2021. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjopen-2020-038954 The Journal's website is at: https://bmjopen.bmj.com/content/11/1/e038954